Brand Value and the Heritage Values of Hoa Lư – Ninh Bình - Van Kim, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 41 No 4DO - 10.25073/2588-1116/vnupam.4579, 2025)
Abstract: In the current context of development, the position of a nation as well as its cultural and brand values have increasingly become vital resources and driving forces in national development strategies. The strength of cultural resources and humanistic values is recognized as a key pillar for the country’s progress. As the capital of the first independent Vietnamese state in the 10th century, Hoa Lư once served as a space for extensive inter-Asian cultural exchanges and interactions. In 2014, the Tràng An Scenic Landscape Complex was inscribed by UNESCO as a World Cultural and Natural Heritage Site under three criteria: Cultural (criterion v), Natural Beauty (criterion vii), and Geology–Geomorphology (criterion viii). It is the first mixed heritage site in Southeast Asia. Alongside its natural heritage, Hoa Lư – Ninh Bình also possesses a wealth of tangible, intangible, and documentary cultural heritages. This article focuses on analyzing the geo-political and geo-cultural position of Hoa Lư – Ninh Bình, its spatial distribution, distinctive features, and outstanding values. It also proposes several solutions to enhance the brand value of various heritage forms, as well as strategies for their sustainable utilization and promotion, approached from an intercultural perspective and in alignment with the vision of a shared natural and cultural heritage of humanity. Keywords: Hoa Lư – Ninh Bình; cultural heritage; values; brand value.